2022
DOI: 10.3389/fphar.2022.934947
|View full text |Cite
|
Sign up to set email alerts
|

Integrated comparative metabolomics and network pharmacology approach to uncover the key active ingredients of Polygonati rhizoma and their therapeutic potential for the treatment of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) has become a worldwide disease affecting human health and resulting in a heavy economic burden on the healthcare system. Polygonati rhizoma (PR), a kind of traditional Chinese medicine (TCM), is known to improve learning and memory abilities. However, its AD-treating material basis and therapeutic potential for the treatment of AD have remained unclear. Therefore, the present study aimed to uncover the key active ingredients of PR and its therapeutic potential for the treatment of AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Wang et al [4] named three of the flavonoids found in PGR which are rutin, syringetin-3-O-glycoside, and isorhamnetin (Figure 1). Scientists extracted 10 chemical components from 10 sections of PGR.…”
Section: Flavonoids In Pgrmentioning
confidence: 99%
“…Wang et al [4] named three of the flavonoids found in PGR which are rutin, syringetin-3-O-glycoside, and isorhamnetin (Figure 1). Scientists extracted 10 chemical components from 10 sections of PGR.…”
Section: Flavonoids In Pgrmentioning
confidence: 99%
“…The neuroprotective effects of PR have also received attention. Studies have shown that PR has pharmacological effects against AD with the mechanism of preventing deposition of the Aβ protein [ 20 ], improving learning and memory function, and reducing neuronal apoptosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delightedly, the researcher used these two techniques to successfully clarify the potential therapeutic effect of PR on COVID-19 and osteoporosis [ 5 , 18 ]. Researchers have combined systematic pharmacology and in vitro and in vivo experimental validation to elucidate the targeted kinase inhibitory activity of PR [ 19 ], and combined with metabolomics, to preliminarily reveal the key active ingredients of PR and its potential for treating Alzheimer’s disease (AD) [ 20 ]. This provides a feasible approach for exploring the mechanism of PR in treating depression.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, network pharmacology has become one of the hot topics in the field of traditional Chinese medicine (TCM) research. Wang et al 28 used a combination of network pharmacology and comparative metabolomics to study the main active ingredients of the Chinese herb Huangjing (Polygonati Rhizoma) and its anti-AD target effects. They further used molecular docking to identify the binding ability of these active ingredients with the AD-related target AChE.…”
Section: The Application Of Bioinformatics In Drug Research For Alzhe...mentioning
confidence: 99%
“…Inhibition of AChE activity, enhancement of neuronal cell vitality, anti-inflammatory effects, and reduction of oxidative stress damage 28…”
Section: The Application Of Bioinformatics In Drug Research For Alzhe...mentioning
confidence: 99%